Listening to and Living With Networked Media During a Pandemic - Soronen, Anne; Talvitie-Lamberg, Karoliina (Imaginations)

(untitled) (York University, 2021)
This article explores mediated listening from the perspective of intimacy during the first weeks of the coronavirus pandemic. The theoretical frame builds on the literature on listening and presence in mediated environments, audience engagement, and intimacy as meaningful connections. Methodologically, the study is connective ethnography, and the data was collected by collaborative autoethnography. Our data show that listening was an individual sensemaking strategy of the outside world and a means to form connectedness. Threading between different screens on digital platforms caused the collapse of public and private contexts, and through these, particular types of intimacy arose. When the position of academic mothers is often that of a ‘knower,’ the severe crisis compels them to look for receptive ways of knowing, such as careful listening of others. Listening is a means to form belonging and understanding, but from a silent position. We should pay more attention to the silent presences and audiences in contemporary mediated environments.